DERADICALIZATION IN INDONESIA : IMPLEMENTATION AND CHALLENGE - Widya, Bella (UI Scholars Hub, 2020)
Deradicalization is a very long and ongoing process. Deradicalization in Indonesia depends on the role of prisons and post-prison reintegration management. Deradicalization in Indonesia has to deal with several obstacles, for example, limited human resources in prisons, lack of coordination between government agencies, the legal frameworks regarding to terrorism crimes have not been comprehensive yet, and others. This can trigger the failure of the process of deradicalization which can lead to recidivist events, community resistance and increasing numbers of radicalism in Indonesia. This study used qualitative research methods with interview data collection techniques and literature study techniques. This research found that the process of deradicalization in Indonesia should be carried out by all levels of society. The process of deradicalization in Indonesia must continue to develop following current patterns of terrorism and it is not limited to deradicalization which is only carried out by terrorist groups based on right-wing ideology. Apart from these problems, the current deradicalization program has also provided many benefits for combating terrorism in Indonesia.